Tribological Performance of 100Cr6/8620 Steel Bearing System under Green Oil Lubrication - Ricardo Ortega-Álvarez; María T. Hernández-Sierra; Luis D. Aguilera-Camacho; Micael G. Bravo-Sánchez; Karla J. Moreno; J. Santos García-Miranda (Metals, 2022)
There is a great need to perform all processes and services more efficiently to reduce energy consumption and material waste. Bearing systems are present in all machines and motors, playing an important role in the reduction of energy consumption. 100Cr6 (ISO 683-17:2014) and AISI 8620 are two typical steels employed in most bearing systems. However, improving the tribological performance of these steels is still required. This study reports the analysis of green lubricants based on mixtures of vegetable oils to improve the friction and wear properties of steel bearing systems. Firstly, a method is presented to identify potential mixtures based on the excess thermodynamic properties. Then, the tribological performance of the 100Cr6/8620 steel bearing system lubricated with the selected mixtures is evaluated by the ball-on-disk method. It was found that the friction and wear behavior of the 100Cr6/8620 steel bearing system can be notably improved by the utilization of oil mixtures rather than pure green oils. The kinetic friction coefficient decreased up to 10% with the ideal mixture of castor and sesame oil, while wear was reduced up to 81% with the ideal mixture of castor and canola oil. Therefore, we suggest that vegetable oil blends may be a good option for the feasible manufacture of biolubricants for bearing systems.